3D Covalent Organic Frameworks Based on Polycyclic Aromatic Hydrocarbons for Reversible Oxygen Capture. Issue 4 (20th January 2021) - Zhang, Minghao; Fang, Jing; Liu, Yaozu; Wang, Yujie; Liao, Li; Tang, Lingxue; Zhu, Liangkui; Qiu, Shilun; Fang, Qianrong
Abstract : Singlet oxygen, as a kind of reactive oxygen species, plays an important role in organic synthesis and biological processes. However, these excited oxygen molecules have a short life and high reactivity; thus it is a great challenge to capture singlet oxygen. Here, for the first time two functionalized 3D covalent organic frameworks (3D COFs) with polycyclic aromatic hydrocarbons, termed as JUC‐575 and JUC‐576, for reversible singlet oxygen capture and release are reported. These 3D COFs, constructed from anthracene or naphthalene derivatives, can effectively trap singlet oxygen through chemical transformation to generate the corresponding endoperoxide COFs (EPO‐COFs). Furthermore, it is also confirmed that the reversible oxygen capture and release between the parent COFs and EPO‐COFs can be well controlled by switching the UV–vis irradiation. This study thus broadens the potential applications of 3D functionalized COFs as molecular carriers in biology and organic synthesis. Abstract : Two 3D functional covalent organic frameworks (COFs) based on polycyclic aromatic hydrocarbons are successfully obtained, which can be converted into corresponding endoperoxide COFs (EPO‐COFs) through the [4 + 2] cycloaddition of 1 O2 under photo‐oxidation. Under UV irradiation, EPO‐COFs can reversibly release oxygen to their parent COFs through the cycloreversion of the peroxidic bond.